LIFE CYCLE ASSESMENT BUDIDAYA UDANG SISTEM MILLENIAL SHRIMP FARMING DI KAWASAN TAMBAK BBPBAP JEPARA - Sumantri, Iwan; Muhammad, Fuad; Hidayat, Jafron Wasiq; Halim, M. Arief Rahman (Program Studi Budidaya Perairan Universitas Mataram, 2023)
With the increasing global population, providing enough food to meet the increasing demand has become a major challenge for the food-producing sectors. Shrimp is a leading commodity in Indonesia, and their production plays an important role in the aquaculture industry. However, shrimp farming causes various types of pollution that damage the environment and aquatic biodiversity, the related impacts must be mitigated to ensure the sustainability of shrimp production. BBPBAP Jepara as an aquaculture technology developer and reviewer institution conducts environmental studies on the technology being developed. This study conducted a life cycle assessment (LCA) on shrimp farming under the Milenila Shrimps Farming system in the Jepara BBPBAB pond area. Midpoint environmental impacts including acidification potential (AP), eutrophication potential (EP) and global warming potential (GWP) were determined. Feed production was identified as the main contributor to AP and GWP for the MSF system, regardless of feed formula. While the environmental performance of feed production is highly dependent on feed conversion ratio, feed ingredients are another determining factor in which animal protein sources, including poultry by-products and fish meal, show a high contribution to AP and GWP. The use of shrimp feed is the largest contributing component of the three impacts, especially with the highest EP. Feed is the highest potential source of impact because the material used has a fish meal component which is the result of marine exploitation which has been quite large so far. In addition, other feed components are agricultural products imported from other countries which are cultivated intensively, one of which is soybean and wheat raw materials, which in their cultivation system still use chemicals and fertilizers intensively.